2023
DOI: 10.3390/ijms241210134
|View full text |Cite
|
Sign up to set email alerts
|

Newly Isolated Virulent Salmophages for Biocontrol of Multidrug-Resistant Salmonella in Ready-to-Eat Plant-Based Food

Abstract: Due to irrational antibiotic stewardship, an increase in the incidence of multidrug resistance of bacteria has been observed recently. Therefore, the search for new therapeutic methods for pathogen infection treatment seems to be necessary. One of the possibilities is the utilization of bacteriophages (phages)—the natural enemies of bacteria. Thus, this study is aimed at the genomic and functional characterization of two newly isolated phages targeting MDR Salmonella enterica strains and their efficacy in salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 98 publications
2
11
0
Order By: Relevance
“…The most sensitive strain was IVIA 1892.1, which was lysed by all the bacteriophages with barely any changes in the OD 600nm values from time 0 to 20–23 h ( Figure 1 A). In the remaining E. amylovora strains, towards the last 3–4 h of the experiment, a slight increase in bacterial populations was observed while being treated with different phages ( Figure 1 B,C), similar to other works [ 70 , 71 ]. This can be explained by the selection of phage-resistant host cell subpopulations under the assayed in vitro conditions [ 22 , 63 , 72 , 73 ].…”
Section: Resultssupporting
confidence: 88%
“…The most sensitive strain was IVIA 1892.1, which was lysed by all the bacteriophages with barely any changes in the OD 600nm values from time 0 to 20–23 h ( Figure 1 A). In the remaining E. amylovora strains, towards the last 3–4 h of the experiment, a slight increase in bacterial populations was observed while being treated with different phages ( Figure 1 B,C), similar to other works [ 70 , 71 ]. This can be explained by the selection of phage-resistant host cell subpopulations under the assayed in vitro conditions [ 22 , 63 , 72 , 73 ].…”
Section: Resultssupporting
confidence: 88%
“…Bacteriophage genomic DNA from lysates was isolated using the PureLink TM RNA/DNA Mini Kit (Thermo Fisher Scientific Inc., Carlsbad, CA, USA) according to the manufacturer’s protocol, with modifications by Wójcicki et al [ 53 ]. The first step was to concentrate the phage lysate by ultracentrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, bacteriophages (phages) have re-gained interest mainly due to their host specificity and bacteriolytic activity against antibiotic-resistant strains and their biofilms [ 313 , 314 , 315 ]. Applying phages in bacterial biofilm eradication involves using naturally occurring strictly virulent or lytic phages that do not encode genes for virulence, toxins or AMR [ 313 , 315 ]. Phage should not be able to mediate horizontal gene transfer or transduce infected bacterial cells [ 316 ].…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%
“…In numerous in vitro biofilm studies, phages have shown their efficacy in penetrating established biofilms and eradicating bacteria [ 321 ], and the effectiveness of single phages and phage cocktails to infect and lyse bacterial cells in single and multispecies biofilms has been confirmed [ 314 , 315 , 316 , 322 ]. Recent reports found that phages are highly effective at in vitro reducing and controlling bacterial biofilms, particularly those formed by S. aureus , K. pneumoniae , Acinetobacter baumannii , P. aeruginosa , Listeria monocytogenes , Salmonella sp., and E. coli [ 40 , 323 , 324 , 325 , 326 ].…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation